2020
DOI: 10.1177/1043986220927123
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Wildlife Crime in Sweden from 2000 to 2017

Abstract: This study combines police records with newspaper articles (media archives) to report the nature and trends of environmental and wildlife crime (EWC) in Sweden from 2000 to 2017. Geographic information systems (GIS) and spatial statistical techniques are used to implement a temporal and spatial analysis of EWC in Swedish municipalities, which are split into three types: urban, accessible rural, and remote rural. Findings show that following the 2006 legal reform that increased possibilities for prosecuting EWC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The use of media coverage, such as digital or daily printed newspapers, as a reference for studying emergency and policing services is not new. Previous researchers have suggested that newspaper articles can be useful in providing a benchmark, an independent record of events that often suffer from unreliable or discontinuous registers (Stassen and Ceccato 2020). Studies show that newspaper articles might underreport some types of events and overestimate others (Marsh 1991;Fine et al 1998;Ghaffar, Hyder, and Bishai 2001).…”
Section: Social Media Data and Emergency During Disasters: From Spatial To Platialmentioning
confidence: 99%
“…The use of media coverage, such as digital or daily printed newspapers, as a reference for studying emergency and policing services is not new. Previous researchers have suggested that newspaper articles can be useful in providing a benchmark, an independent record of events that often suffer from unreliable or discontinuous registers (Stassen and Ceccato 2020). Studies show that newspaper articles might underreport some types of events and overestimate others (Marsh 1991;Fine et al 1998;Ghaffar, Hyder, and Bishai 2001).…”
Section: Social Media Data and Emergency During Disasters: From Spatial To Platialmentioning
confidence: 99%
“…Although rural criminology is a growing field of research (Harkness, 2020;Meško, 2020), the knowledge about 'ordinary' rural crimes in international contexts still remains incipient compared with other fields (but see Ceccato, 2015aCeccato, , 2015bDonnermeyer, 2016). If we extend the focus to account for events that are not defined by law as crimes but still cause harm (Hillyard & Tombs, 2007) against wildlife, environment or people, then a variety of issues in need of further research emerges (e.g., Favarin, 2020;Stassen & Ceccato, 2020;von Essen et al, 2014). The adoption of the concept of 'harm' enables us to move beyond legal definitions of 'crime' to include immoral, wrongful, and injurious acts that are not necessarily illegal but may lead to injury or damage to individuals or society, either intentionally or because of negligence.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently, Nobles (2019) has argued that this aforesaid point about the lack of suitable data sets has been overstated, and that in fact there are a variety of secondary data readily accessible through which to investigate many aspects of different justice systems' responses to environmental crimes. While this is indeed true with respect to the United States, it is not necessarily the case in other countries across the world Stassen & Ceccato, 2020). Both Lynch et al (2017) and Lynch and Pires (2019) have recently lamented the scarce attention that has been directed toward quantitative analyses of relevant environmental crimes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the principal obstacles to conducting empirical research on IWT is the dearth—and poor quality—of publicly available data on waste crimes, illegal waste shipments, the prices that are charged on the illegal market as well as on the licit waste market (e.g., production, treatment, import, and export). Many authors and institutions have noted this problem and stressed the need to improve both data collection and data availability within the field of environmental crime to aid future research (Bisschop, 2012; Gibbs & Simpson, 2009; Greife & Maume, 2020; Stassen & Ceccato, 2020). However, more recently, Nobles (2019) has argued that this aforesaid point about the lack of suitable data sets has been overstated, and that in fact there are a variety of secondary data readily accessible through which to investigate many aspects of different justice systems’ responses to environmental crimes.…”
Section: Introductionmentioning
confidence: 99%